Ongoing Fen–Bog Transition in a Boreal Aapa Mire Inferred from Repeated Field Sampling, Aerial Images, and Landsat Data - Kolari, Tiina H. M.; Sallinen, Antti; Wolff, Franziska; Kumpula, Timo; Tolonen, Kimmo; Tahvanainen, Teemu (Ecosystems, 2022)
Northern aapa mire complexes are characterized by patterned fens with flarks (wet fen surfaces) and bog zone margins with Sphagnum moss cover. Evidence exists of a recent increase in Sphagnum over fens that can alter ecosystem functions. Contrast between flarks and Sphagnum moss cover may enable remote sensing of these changes with satellite proxies. We explored recent changes in hydro-morphological patterns and vegetation in a south-boreal aapa mire in Finland and tested the performance of Landsat bands and indices in detecting Sphagnum increase in aapa mires. We combined aerial image analysis and vegetation survey, repeated after 60 years, to support Landsat satellite image analysis. Aerial image analysis revealed a decrease in flark area by 46% between 1947 and 2019. Repeated survey showed increase in Sphagnum mosses (S. pulchrum, S. papillosum) and deep-rooted vascular plants (Menyanthes trifoliata, Carex rostrata). A supervised classification of high-resolution UAV image recognized the legacy of infilled flarks in the patterning of Sphagnum carpets. Among Landsat variables, all separate spectral bands, the Green Difference Vegetation Index (GDVI), and the Automated Water Extraction Index (AWEI) correlated with the flark area. Between 1985 and 2020, near-infrared (NIR) and GDVI increased in the central flark area, and AWEI decreased throughout the mire area. In aapa mire complexes, flark fen and Sphagnum bog zones have contrasting Landsat NIR reflectance, and NIR band is suggested for monitoring changes in flarks. The observed increase in Sphagnum mosses supports the interpretation of ongoing fen–bog transitions in Northern European aapa mires, indicating significant ecosystem-scale changes.